Kontribusi Kelincahan Dan Kecepatan Terhadap Kemampuan Menggiring Bola Pemain Sepak Bola Di SMA Negeri 7 Bengkulu Selatan - Aditya Putra Ananta; Asnawai Asnawai; Dody Ertanto (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aimed to determine the contribution of agility and speed to the dribbling ability of soccer players at SMA Negeri 7 Bengkulu Selatan. The research employed a correlational quantitative design. The population consisted of all soccer players participating in extracurricular activities at SMA Negeri 7 Bengkulu Selatan, with the sample selected using a total sampling technique. Agility was measured using the Illinois Agility Test, speed was measured using the 30-meter sprint test, and dribbling ability was assessed through a soccer dribbling test. Data were analyzed using descriptive statistics, correlation analysis, and multiple regression analysis to determine both the partial and simultaneous contributions of agility and speed to dribbling ability. The results showed that agility had a significant contribution to dribbling ability, speed also contributed significantly to dribbling performance, and agility and speed simultaneously provided a significant contribution to the dribbling ability of soccer players. Players with better agility and higher speed tended to demonstrate more effective ball control while dribbling during play. These findings indicate that agility and speed are important physical components that support dribbling performance in soccer. In conclusion, agility and speed contribute significantly to the dribbling ability of soccer players at SMA Negeri 7 Bengkulu Selatan. Therefore, coaches and physical education teachers are recommended to incorporate agility and speed training programs to improve players’ dribbling performance and overall soccer skills.